Implikasi Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 terhadap Demokrasi di Indonesia - Rohman Rohman (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
The inconsistency in case rulings and its impact on the principles of separation of powers and the quality of democracy in Indonesia. The case challenges the age limit for presidential and vice-presidential candidates, with the Constitutional Court acknowledging the legal standing of the petitioner despite discrepancies in the outcomes of similar cases. The implications of adding norms in such rulings also raise questions about the legitimacy of Constitutional Court decisions in the political context. This study employs qualitative methods, leading to the conclusion that the decision results in controversy among the public, causing them to lose trust in the constitutional court due to autocratic rulings benefiting political elite. Keywords: Constitutional Court, Democracy.